Bibliometric Analysis Of Flexing Phenomenon In The Digital Era - Fuja Dastiana; Rozalinda Rozalinda; Testru Hendra (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the development of studies on the phenomenon of flexing in the digital era and map the main topics that have become the focus of research over the past decade. The phenomenon of flexing, which refers to the behavior of showing off wealth, achievements, or lifestyle on social media, has become an important issue in digital social and economic studies because it is related to consumptive behavior, self-image, and the dynamics of interaction in virtual spaces. The method used in this study is bibliometric analysis, with publication data from the period 2015–2025 which produced 343 articles obtained from relevant scientific databases. The data were analyzed using VOSviewer software to visualize keyword networks, relationships between authors, and thematic clusters. Publication trend analysis was also conducted to observe the development of the number of researches each year. The results of the study showed a significant increase in the number of publications related to flexing, especially starting in 2020 and reaching its peak in 2022. Bibliometric visualization identified four main objectives, namely (1) flexing and consumer lifestyle, (2) personal branding and digital identity, (3) digital literacy and ethics, and (4) social psychology perspectives related to validation needs. The keyword network shows that the terms “ human ” and “ social media digitalization ” are the center of connection in the research. Overall, this study provides a comprehensive overview of the direction of flexing research development and opens up opportunities for further research on the psychological, social and ethical impacts of digital in the future.